Problems of historical and spiritual continuity in the work Magzhan Zhumabaev (Journal of Philosophy Culture and Political Science, 2018)
This article analyzes the ideas of the poet about the history of philosophy from a position on the basis of works Magzhan Zhumabaev. This article describes the mechanism based formation of historical existents and consciousness based on the outlook Magzhan Zhumabaev on its evaluation of numerous historical figures, his analytical vision on the past, present, and future. Also defines the role of historical consciousness in the development of societies. Magzhan Zhumabaev being a poet is not only understood, but also responsibility of the people. He was deeply troubled peoples problem and bard in his poems raise topical issues of his time, and tried to convey to the readers. Akin felt right ways and means of self-preservation of the nation and worried about the future of his people. Verses «Turkistan» and «Turan» Magzhan Zhumabaev appreciates the role of historical consciousness in the implementation of the above lofty goals. Key words: Historical existence, consciousness, Turkistan, Alash, national history, fate of the people.